2023
DOI: 10.3390/molecules28166032
|View full text |Cite
|
Sign up to set email alerts
|

Scaffold Morphing and In Silico Design of Potential BACE-1 (β-Secretase) Inhibitors: A Hope for a Newer Dawn in Anti-Alzheimer Therapeutics

Abstract: Alzheimer’s disease (AD) is the prime cause of 65–80% of dementia cases and is caused by plaque and tangle deposition in the brain neurons leading to brain cell degeneration. β-secretase (BACE-1) is a key enzyme responsible for depositing extracellular plaques made of β-amyloid protein. Therefore, efforts are being applied to develop novel BACE-1 enzyme inhibitors to halt plaque build-up. In our study, we analyzed some Elenbecestat analogues (a BACE-1 inhibitor currently in clinical trials) using a structure-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Notably, Alzheimer’s disease is a neurodegenerative disorder disease correlated with the accumulation of amyloid plagues of Aβ 40 and Aβ 42 peptides, and the hallmark of the mentioned neurodegenerative disease exceedingly depends on cerebral formation of Aβ 40 and Aβ 42 peptides with 38–43 amino acid length and subsequent aggregation formation . It is worthy to note that the toxic amyloid-β peptides are generated by processing the β-amyloid precursor protein with β-amyloid cleaving enzyme 1 (BACE-1) and γ-secretase, which constitutes the first step in the APP degradation accompanied by production of the C99 fragment (a membrane-bound C-terminal) and a soluble fragment (sAPPβ) . Because of the remarkable role of BACE-1 in the cleavage of APP, inhibition of functional activity of BACE-1 has been a prospective approach of a disease-modifying therapy for patients who are at risk of developing Alzheimer’s disease .…”
Section: Resultsmentioning
confidence: 99%
“…Notably, Alzheimer’s disease is a neurodegenerative disorder disease correlated with the accumulation of amyloid plagues of Aβ 40 and Aβ 42 peptides, and the hallmark of the mentioned neurodegenerative disease exceedingly depends on cerebral formation of Aβ 40 and Aβ 42 peptides with 38–43 amino acid length and subsequent aggregation formation . It is worthy to note that the toxic amyloid-β peptides are generated by processing the β-amyloid precursor protein with β-amyloid cleaving enzyme 1 (BACE-1) and γ-secretase, which constitutes the first step in the APP degradation accompanied by production of the C99 fragment (a membrane-bound C-terminal) and a soluble fragment (sAPPβ) . Because of the remarkable role of BACE-1 in the cleavage of APP, inhibition of functional activity of BACE-1 has been a prospective approach of a disease-modifying therapy for patients who are at risk of developing Alzheimer’s disease .…”
Section: Resultsmentioning
confidence: 99%
“…Synthetic accessibility was used for arranging the derived ZDWX-25 analogs. Synthetic accessibility is graded on a scale of 1 (very easy) to 10 (very difficult) [22][23][24]. The generated analogues were screened using a threshold of 2.4, and the chosen compounds continued to undergo in silico pharmacokinetic tests.…”
Section: Scaffold Morphingmentioning
confidence: 99%
“…Thus, it is hypothesized that basil could have potential neuroprotective compounds. However, investigations studying the detailed effect of basil components on the crucial biochemical targets such as AChE, GSK3β, γ-secretase, and sirtuin2 of dementia are scanty [26][27][28][29][30][31][32][33]. Thus, the present study was designed to study the detailed mechanism of action of previously identified bioactive compounds in basil using silico techniques.…”
Section: Introductionmentioning
confidence: 99%